Gradient-extended two-surface damage-plasticity: Micromorphic formulation and numerical aspects. (October 2017) - Brepols, Tim; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: A regularized gradient-extended damage-plasticity model is discussed which is based on a micromorphic approach in the spirit of Forest (2009). Damage and plasticity are treated as independent but strongly coupled dissipative phenomena by means of a 'two-surface' formulation, i.e. by using separate yield and damage functions as well as appropriate loading/unloading conditions. By means of two independent dissipation potentials for plasticity and damage, thermodynamically consistent evolution equations are derived. The model accounts for nonlinear plastic as well as damage hardening. The models' implementation at the local integration point level, both using a local active set search strategy known from multisurface plasticity and a recent approach based on a reformulation of the model equations by means of the Fischer-Burmeister complementarity function, is discussed in detail. It is shown how the model can be implemented into finite elements and the four algorithmically consistent tangent operators are presented which are necessary to obtain quadratic convergence in a global Newton scheme. Various numerical benchmark tests performed in the study nicely indicate the model's ability to deliver mesh-independent results in coupled damage-plasticity finite element simulations. Highlights: A gradient-extended damage-plasticity model based on the micromorphic approach according to Forest (2009, 2016) is presented. Damage and plasticity are treated as distinct but coupled dissipative mechanisms by means of a 'two-surface' methodology. Two algorithms based on a local active set search strategy or the Fischer-Burmeister complementarity function are discussed. Consistent tangent operators necessary for a quadratic rate of convergence at the global finite element level are presented. Various benchmark tests illustrate the model's mesh regularization abilities in finite element simulations involving damage.